Synthesis, Structure Elucidation, Antibacterial Activities, and Synergistic Effects of Novel Juglone and Naphthazarin Derivatives Against Clinical Methicillin-Resistant Staphylococcus aureus Strains - Duvauchelle, Valentin; Majdi, Chaimae; Bénimélis, David; Dunyach-Remy, Catherine; Meffre, Patrick; Benfodda, Zohra (Frontiers in Chemistry, 2021)
Infections caused by drug-resistant bacteria are a serious threat to human and global public health. Moreover, recent years very few antibiotics have been discovered and developed by pharmaceutical companies. Therefore, there is an urgent need to discover and develop new antibacterial agents to combat multidrug-resistant bacteria. In this work, two novel series of juglone/naphthazarin derivatives (43 compounds) were synthesized and evaluated for their antibacterial properties against various clinical and reference Gram-positive MSSA, clinical Gram-positive MRSA and clinical and reference Gram-negative bacteria E. coli and P. aeruginosa. These strains are of clinical importance because they belong to ESKAPE pathogens. Compounds 3al, 5ag and 3bg showed promising activity against clinical and reference MSSA (MIC: 1 – 8 µg/mL) and good efficacy against clinical MRSA (MIC: 2 – 8 µg/mL) strains. 5am and 3bm demonstrated better activity on both MSSA (MIC: 0.5 µg/mL) and MRSA (MIC: 2 µg/mL) strains. Their MICs were similar to those of cloxacillin against clinical MRSA strain. Synergistic effects of active compounds 3al, 5ag, 5am, 3bg and 3bm were evaluated with reference antibiotics and exhibited that the antibiotic combination with 3bm efficiently enhanced the antimicrobial activity. Compound 3bm was found to restore the sensitivity of clinical MRSA to cloxacillin and enhanced the antibacterial activity of vancomycin when they were added together. In presence of 3bm, MICs values of vancomycin and cloxacillin were lowered up to 1/16th of the original MIC with a FIC index of 0.313. Moreover, compounds 3al, 5ag, 5am, 3bg and 3bm did not present hemolytic activity on sheep red blood cell. In silico prediction of ADME profile parameters results for 3bm are promising and heartening for further development.